The most useful technological tools in virtual education - Campos Gómez, Jocelyn Abigail
This report is a brief summary of the contents developed during the specialization course. Topics related to the different virtual tools that the teacher can use to carry out classes virtually were developed, as well as in distance education and online education. The objectives pursued by this course are to train students in the practical and real use of cybernetic tools and platforms that allow them both in the present and in the future to provide and effective teaching in a virtual way. Nowadays on the web we can find such complete tools that allow us to teach classes, evaluate, create tasks, create didactic material and all in a virtual way within a click. This is where we can see the importance of the knowledge and effective management of these applications, since in the current world the virtual modality has become the main source of development of communications both in the area of education and in the work area and this was demonstrated precisely with the experience that the entire world has lived with the COVID-19 pandemic. Keys words: Teaching ; tolos ; Applications ; Online ; Education ; Resources.